Integrated farming system: A holistic approach to sustainable agriculture - Singh, Kuldeep; Walia, S. S.; Kumar, Pankaj; Singh, Parminder (Indian Farming, 2025)
Modern agriculture faces multiple challenges, including food security, nutritional adequacy, sustainability, and profitability, exacerbated by a rapidly growing population and environmental concerns. Integrated Farming Systems (IFS) offer a holistic, eco-friendly, and cost-effective approach that combines traditional knowledge with modern technology to address these issues. IFS integrates various farm enterprises—crops, livestock, forestry, and more—to improve resource-use, productivity, and profitability for small and marginal farmers. This study highlights the economic and ecological benefits of IFS across six farms, demonstrating improved returns, diversified food products, and enhanced resilience against environmental stresses under The Farmer FIRST Programme. The findings underscore the need for supportive policies to foster widespread adoption of IFS, ensuring sustainable agricultural practices that meet future food demands while contributing to environmental conservation.